2018
DOI: 10.1080/15548627.2018.1556946
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 (toll-like receptor 4) activation suppresses autophagy through inhibition of FOXO3 and impairs phagocytic capacity of microglia

Abstract: Macroautophagy/autophagy is a lysosome-dependent catabolic process for the turnover of proteins and organelles in eukaryotes. Autophagy plays an important role in immunity and inflammation, as well as metabolism and cell survival. Diverse immune and inflammatory signals induce autophagy in macrophages through pattern recognition receptors, such as toll-like receptors (TLRs). However, the physiological role of autophagy and its signaling mechanisms in microglia remain poorly understood. Microglia are phagocytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
135
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(155 citation statements)
references
References 86 publications
(105 reference statements)
17
135
2
1
Order By: Relevance
“…Although it has been reported that LPS upregulates autophagy via the receptor TLR4 in RAW264.7 cells [46], Lee et al and He et al observed that autophagy was inhibited in LPSinduced BV2 microglia, which is consistent with our results [33,47]. The study of Lee et al and He et al also examined the effect of LPS on autophagy in RAW264.7 cells and revealed a differential LC3 response to LPS between microglial BV2 cells, in which autophagy was downregulated, and RAW264.7 cells, in which autophagy was upregulated [47]. The researchers speculated that the mechanism of autophagy inhibition may be dependent on cell type or even the state of cells of the same type.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although it has been reported that LPS upregulates autophagy via the receptor TLR4 in RAW264.7 cells [46], Lee et al and He et al observed that autophagy was inhibited in LPSinduced BV2 microglia, which is consistent with our results [33,47]. The study of Lee et al and He et al also examined the effect of LPS on autophagy in RAW264.7 cells and revealed a differential LC3 response to LPS between microglial BV2 cells, in which autophagy was downregulated, and RAW264.7 cells, in which autophagy was upregulated [47]. The researchers speculated that the mechanism of autophagy inhibition may be dependent on cell type or even the state of cells of the same type.…”
Section: Discussionsupporting
confidence: 93%
“…Here, we found that the expression of Vps34 was significantly inhibited in LPS-stimulated microglia. These results are consistent with a recent metabolomics analysis in microglia which showed that LPS induced a reduction in the synthesis of PI(3)P [47]. Therefore, it appears that LPS impairs autophagic flux in microglia by reducing the formation of autophagosomes.…”
Section: Discussionsupporting
confidence: 92%
“…LPS is widely used to induce neuroin ammation [2,3,49,54,62]. Numerous studies showed that LPS treatment could induce central in ammatory response associated with proin ammatory cytokines production, glial cell activation, as well as ROS and RNS generation [2,5,7,40,44,47,54,[63][64][65][66][67][68][69]. Furthermore, activated NF-κB also promotes neurotoxic cytokines and ROS production of glial cells [2,3,5].…”
Section: Discussionmentioning
confidence: 99%
“…LPS triggers in ammatory responses in humans and other mammals. Many papers reported that LPS promoted phagocytosis (48)(49)(50), while some studies showed an inhibitory effect of LPS on phagocytosis (51)(52)(53). We demonstrated that LPS signi cantly enhanced the production of TNF-α in microglia and inhibited PON1 KO-induced phagocytosis.…”
Section: Discussionmentioning
confidence: 99%